Competencies of caregivers as support to children with developmental disabilities - Go, Marquez (2008)
This research qualitatively developed a list of competencies for caregivers who serve children with developmental disabilities. It was conducted using 3 methods of data gathering: focus group discussions, interviews and qualitative surveys. It involved 64 respondents who were parents, caregivers and teachers of children with developmental disabilities from private schols in Quezon City. Findings showed caregiver strategies and motivations that influenced the conduct of these tasks. Love, as the caregiver's main motivation, was mentioned repeatedly across the 3 research methods. It was considered as a crucial matter in the care of children with developmental disabilities.
Thesis (M.A. Special Education)--University of the Philippines, Diliman.
Keywords: Developmentally disabled children -- Home care -- Philippines -- Quezon City; Children with disablities -- Home care -- Philippines -- Quezon City; Caregivers -- Rating of -- Philippines -- Quezon City